Community Perceptions in the Border Areas Regarding the Main Points of Agreement Concerning Final Completion of The Land Border Between Ri-Rdtl (Case Study in Haumeniana Village, District Bikomi Nilulat North Central Timor District) - LAKE, Primus; DAENG, Ernawati; FALLO, Adriana R.; RIHI, David Wilfrid; PENI, Andreas; ROHI, Bertjilistriani Lodo; TUTHAES, Lydia Carolina (PT Keberlanjutan Strategis Indonesia, 2024)
This research was motivated by the incomplete completion of the RI – RDTL state boundary in the Oekusi enclave area. Three segments are still problematic: the Noelbesi - Citrana segment, the Bijaelesunan - Oben segment, and the Haumeniana - Pasabe segment. On July 22, 2019, Wiranto (Coordinating Minister for Political, Legal and Security Affairs of the Republic of Indonesia) and Kay Rala The contents of the Agreement, among other things, stipulate that the Neolbesi – Citrana segment be divided into two, the Bijaelesunan – Oben segment to be completed by the 1904 Agreement between the Dutch and the Portuguese, and for the Haumeniana – Pasabe segment the boundary is determined by adjusting the line along the road according to the coordinate points of both parties. It will be determined later. This research was carried out in Haumeniana village, Bikomi Nilulat sub-district, North Central Timor district, focusing on the perceptions of the Haumeniana village community regarding the contents of the Wiranto. This means that the disputed area all belongs to RDTL. This research uses a descriptive qualitative approach. Data collection used interviews, observation and FGD techniques. This research concluded that all primary informants and FGD participants from elements of the Haumeniana community had negative perceptions of the contents of the Wiranto – Xanana Agreement.